2022
DOI: 10.21037/atm-21-6272
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical characteristics of hepatitis B surface antigen-negative/hepatitis B core antibody-positive patients with detectable serum hepatitis B virus DNA

Abstract: Background: To determine the prevalence of detectable serum hepatitis B virus (HBV) DNA in patients who are hepatitis B surface antigen (HBsAg)-negative and hepatitis B core antibody (HBcAb)-positive. The correlation between HBV DNA viral load and serological markers, as well as liver and coagulation function indicators were investigated. Furthermore, the effects of immunosuppressive therapy on DNA replication were assessed. Methods: A total of 2,013 HBsAg-negative/HBcAb-positive patients admitted to our hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In the serological diagnosis of OBI, many experts and guidelines currently recommend a highly sensitive HBV DNA method with a lower limit of detection (10-20 IU/ml) (which should actually be the lower limit of quantification, author’s note), a wider linear range, and a higher specificity. However, due to the fact that HBV DNA in OBI patients is usually <200 IU/ml, of which 80%-90% is <20 IU/ml, with intermittent elevation/positive characteristics, along with the impact of test efficacy and method, serum/plasma extraction volume, sample volume, genotype coverage, internal standard setting and cost differences, facing shortcomings such as nucleic acid contamination, lack of industry regulation and standardization, thus the limitations of serum HBV DNA testing for OBI diagnosis are evident ( Kang et al., 2014 ; Morales-Romero et al., 2014 ; Raimondo et al., 2019 ; Cai et al., 2022 ), the most prominent of which is the sensitivity of the assay.…”
Section: Limitation Of Obi Serologic Diagnosis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the serological diagnosis of OBI, many experts and guidelines currently recommend a highly sensitive HBV DNA method with a lower limit of detection (10-20 IU/ml) (which should actually be the lower limit of quantification, author’s note), a wider linear range, and a higher specificity. However, due to the fact that HBV DNA in OBI patients is usually <200 IU/ml, of which 80%-90% is <20 IU/ml, with intermittent elevation/positive characteristics, along with the impact of test efficacy and method, serum/plasma extraction volume, sample volume, genotype coverage, internal standard setting and cost differences, facing shortcomings such as nucleic acid contamination, lack of industry regulation and standardization, thus the limitations of serum HBV DNA testing for OBI diagnosis are evident ( Kang et al., 2014 ; Morales-Romero et al., 2014 ; Raimondo et al., 2019 ; Cai et al., 2022 ), the most prominent of which is the sensitivity of the assay.…”
Section: Limitation Of Obi Serologic Diagnosis Methodsmentioning
confidence: 99%
“…(2010) revealed that the rate of OBI detection among isolated anti-HBc positive individuals by serological methods was only 0.091% ( Table 2 ). Cai et al. (2022) showed that the positive rate of HBV DNA detection in the serum of HBsAg(-)/anti-HBc(+) patients was 5.4% (108/2013)(see more details in Table 2 ).…”
Section: Limitation Of Obi Serologic Diagnosis Methodsmentioning
confidence: 99%
“…Therefore, it can be considered that individuals with anti-HBe positivity may be in a partial immune clearance stage. The detection rate of OBI in the anti-HBe positive group (15.61%, 32/205) was significantly higher than that in the anti-HBe negative group (3.73%, 10/268) (P < 0.05) 19 . This suggests that even among IAHBc individuals, it is possible to further classify them into two different states based on the presence or absence of anti-HBe, which may have different clinical implications.…”
Section: Discussionmentioning
confidence: 70%
“…If the focus is on OBI, it is important to further examine the anti-HBe status. Studies, such as Cai et al 19 , have shown that OBI has the highest detection rate in IAHBc cases where both anti-HBc and anti-HBe are positive (15.61%, 32/205). This aligns with the findings of this study, suggesting that if anti-HBe is still positive, it may indicate an early stage of partial immune activation and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, AST was also could be as a marker reflecting liver damage. A previous study has reported that the level of AST could reflect the HBV DNA level [29], however, it wasn't the independent risk factor in predicting the HBV DNA level in this study and it needed further research.…”
Section: Discussionmentioning
confidence: 58%